THE EFFECT OF EDUCATION LEVEL, WORK PERIOD AND INFORMATION TECHNOLOGY ON SERVICE QUALITY AND JOB SATISFACTIONAS AN INTERVENING VARIABLE IN VILLAGE DEVICES ON KUNDUR ISLAND KARIMUN DISTRICT - Afrizal, Afrizal; Ngaliman, Ngaliman; Satriawan, Bambang; Khaddafi, Muammar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study was to determine and analyze the effect of education level, years of service and information technology on service quality and job satisfaction as an intervening variable for village officials on Kundur Island, Karimun Regency. The method used was a questionnaire and distributed to 122 respondents. statistical data analysis using SEM PLS (structuralequation modellingpartial least squares) and using path analysis to examine the pattern of the relationship between the influence of the dependent and independent variables, both direct and indirect effects with smart pls 3.0 software. The research results showeducation level has a direct effect on job satisfaction with a p-value of 0.000, tenure has an indirect effect on job satisfaction with a p-value of 0.658, information technology education level has a direct effect on job satisfaction with a p-value of 0.000, job satisfaction has a direct effect on service quality with a p-value of 0.001, education level has a direct effect on service quality with a p-value of 0.008, tenure has a direct effect on service quality with a p-value of 0.009, information technology has a direct effect on service quality with a p-value of 0.018 , job satisfaction mediates the relationship between education level and service quality with a p-value of 0.009 <0.05,Job satisfaction mediates the relationship between tenure and service quality with a p-value of 0.006 <0.05, and job satisfaction mediates the relationship between information technology and service quality with a p-value of 0.004 <0.05.